PRESSURE-VOLUME-TEMPERATURE EQUATION OF STATE OF ANDRADITE AND GROSSULAR, BY HIGH-PRESSURE AND -TEMPERATURE POWDER DIFFRACTION - Pavese A.; Diella V.; Pischedda V.; Merli M.; Bocchio R.; Mezouar M. (My University, 2001)
The thermoelastic parameters of natural andradite and grossular have been investigated by high-pressure and -temperature synchrotron X-ray powder diffraction, at ESRF, on the ID30 beamline. The P–V–T data have been fitted by Birch-Murnaghan-like EOSs, using both the approximated and the general form. We have obtained for andradite K 0=158.0(±1.5) GPa, (dK/dT )0=−0.020(3) GPa K−1 and α0=31.6(2) 10−6 K−1, and for grossular K 0=168.2(±1.7) GPa, (dK/dT)0=−0.016(3) GPa K−1 and α0=27.8(2) 10−6 K−1. Comparisons between the present issues and thermoelastic properties of garnets earlier determined are carried out.
Keywords: ANDRADITE; GROSSULAR; T EOS; X-RAY POWDER DIFFRACTION